Analisis Keputusan Pembelian Ditinjau Dari Citra Toko dan Variasi Produk : (Survei pada Konsumen Kareem Hjiab di Kab.Tasikmalaya) - Fahrul Riza Fauzi; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect simultaneously and partially of store image and product variations on purchase decision Kareem Hjiab in Kab, Tasikmalaya City. The method used in this research is method a survey. The research data were obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple regression analysis using SPSS software. The results of this study indicate that the store image and product variations simultaneously have a significant effect on purchase decision. Store image partially significant effect on purchase decision. product variations has a significant effect on purchase decision Kareem Hjiab.